2022
DOI: 10.1590/2177-6709.27.6.e2221219.oar
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and financial impact of the COVID-19 pandemic during the first stages of the pandemic: Brazilian orthodontists´ perspective

Abstract: Introduction: Brazil faced a catastrophic situation in the coronavirus pandemic. Due to the high risk of contamination and spread of COVID-19, dentist have been attending only urgency and emergency services in Brazil at the beginning of the pandemic. Objective: This research aimed to evaluate the psychological and financial impacts caused by the coronavirus pandemic in Brazilian orthodontists. Methods: This population-based cross-sectional study collected demographic data and mental health measurements from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
(115 reference statements)
0
1
0
Order By: Relevance
“…Healthcare workers (HCWs) are at risk for developing sleep problems compared to the general population due to their heavy workload and high-stress levels, which can be exacerbated during a pandemic or other health crisis. 1 4 A recent meta-analysis found that HCWs had a significantly higher prevalence of insomnia compared to non-HCWs throughout the pandemic. 5 Concerningly, compared to the initial months of the pandemic, HCWs’ sleep quality has progressively worsened and has been associated with psychiatric symptoms such as acute stress, depression, and anxiety symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare workers (HCWs) are at risk for developing sleep problems compared to the general population due to their heavy workload and high-stress levels, which can be exacerbated during a pandemic or other health crisis. 1 4 A recent meta-analysis found that HCWs had a significantly higher prevalence of insomnia compared to non-HCWs throughout the pandemic. 5 Concerningly, compared to the initial months of the pandemic, HCWs’ sleep quality has progressively worsened and has been associated with psychiatric symptoms such as acute stress, depression, and anxiety symptoms.…”
Section: Introductionmentioning
confidence: 99%